IMPROVING STUDENTS’ READING COMPREHENSION OF NARRATIVE TEXT THROUGH DRAW STRATEGY - Riska; Usman, Sriati; Mukrim, Mukrim (e-Journal of ELTS (English Language Teaching Society), 2023)
The objective of this research is to investigate whether or not the use of DRAW Strategy is effective to develop reading comprehension of second grade students at SMP Negeri Satap Parigi Tengah. The method of this research was pre-experimental research design with one group pre-test post-test only. Since the sample of the research only one class, the researcher applied total sampling technique. The total number of students were 12. The instrument of data collection was test which administered twice called pre-test and post-test. The data were analyzed descriptively and statistically. The result of data analysis showed that there is significant difference between the students’ achievement on pre-test and post-test. The students’ mean score on the pre-test increase from 42.2 to 81,62 on the post-test. By applying 0.05 significant level with 11 degree of freedom, it was found that the value of t-counted (46.53) is greater than the value of t-table (1.796). It indicates that the research hypothesis is accepted. Thus, the application of DRAW Strategy is effective to improve reading of the eighth grade students at SMP Negeri Satap Parigi Tengah.